COVD-31. THE STATE OF NEURO-ONCOLOGY DURING THE COVID-19 PANDEMIC: A WORLDWIDE ASSESSMENT - Mrugala, Maciej (Neuro Oncol, 2020)
To assess the impact of the pandemic on the field, we performed an international web-based survey of practitioners, scientists, and trainees from 21 neuro-oncology organizations across 6 continents from April 24 through May 17. Of 582 respondents, 258 (45%) were in the US, and 314 (55%) were international. 80.4% were affiliated with academic institutions. 94% respondents reported changes in clinical practice; 95% reported conversion to telemedicine for at least some appointments. However, almost 10% practitioners felt the need to see patients in person specifically because of billing concerns and perceived institutional pressure. Over 50% believed neuro-oncology patients were at increased risk of contracting COVID-19. 67% practitioners suspended enrollment for at least one clinical trial: 53% suspended phase II and 62% suspended phase III trial enrollment. 71% clinicians feared for their or their families’ safety, specifically because of their clinical duties. 20% percent said they did not have enough PPE to work safely; about the same percentage were unhappy with their institutions’ response to the pandemic. 43% believed the pandemic would negatively affect their academic career, and 52% fellowship program directors were worried about losing funding for their training programs. While 69% respondents reported increased stress, 44% were offered no psychosocial support. 37% had their salary reduced. 36% researchers had to temporarily close their laboratories. In contrast, the pandemic created positive changes in perceived patient and family satisfaction, quality of communication, and use of technology to deliver care and interactions with other practitioners. CONCLUSIONS: The pandemic has altered standard treatment schedules and limited investigational treatment options for patients. In some cases, clinicians felt institutional pressure to continue conducting billable in-person visits when telemedicine visits would have sufficed. A lack of institutional support created anxiety among clinicians and researchers. We make specific recommendations to guide clinical and scientific infrastructure moving forward.